Solar mediated reduction of graphene oxide. Issue 2 (4th January 2017) - Mohandoss, Manonmani; Gupta, Soujit Sen; Nelleri, Anith; Pradeep, T.; Maliyekkal, Shihabudheen M.
Abstract : This paper explores the reduction of water dispersed graphene oxide (GO) by sunlight. The electronic and structural properties of the sunlight reduced GO are compared with that of GO reduced by conventional methods. Abstract : This paper explores the reduction of water dispersed graphene oxide (GO) by sunlight as an environmentally friendly alternative to conventional methods of reduction of GO. The possible mechanism of the reduction process is delineated. The electrical and thermal conductivity, the degree of reduction and structural defects of sunlight reduced GO (sRGO) are studied thoroughly and compared with RGO samples produced through hydrazine (hRGO) and hydrothermal (hyRGO) reduction routes. The study reveals that the production of sRGO is feasible and its electronic properties are on a par with those of hRGO. Interestingly, sRGO showed the least structural defects, good dispersibility and higher conductivity vis-a-vis its counterparts. This cost effective and environmentally friendly method of reducing GO to RGO with enhanced electronic properties may find applications in bio-sensing and electrochemical energy storage devices.